2011
DOI: 10.1254/jphs.11r01cp
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Hydrogen Sulfide Production in the Pancreatic β-Cell

Abstract: Abstract.Hydrogen sulfide (H 2 S) is an important signaling molecule in various mammalian cells and tissues. H 2 S is synthesized from L-cysteine and regulates several cellular and physiological phenomena (vasorelaxation, hormone secretion, and apoptosis) and multicellular events (neuro modulation and inflammatory responses). H 2 S can be produced in pancreatic β-cells by cystathionine β-synthase (CBS) or cystathionine γ-lyase (CSE). H 2 S inhibits insulin release and regulates β-cell survival. We found that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
(47 reference statements)
1
22
0
Order By: Relevance
“…They also found that NaHS was able to suppress ROS production induced by cytokines or hydrogen peroxide, via activation of Akt signaling (90,197,198). These findings are consistent with the effect of DATS (a hydrogen sulfide precursor, see below) on the level of blood sugar and oxidative stress markers in rats with type II diabetes mellitus (54).…”
Section: Diabetes and Metabolismsupporting
confidence: 69%
“…They also found that NaHS was able to suppress ROS production induced by cytokines or hydrogen peroxide, via activation of Akt signaling (90,197,198). These findings are consistent with the effect of DATS (a hydrogen sulfide precursor, see below) on the level of blood sugar and oxidative stress markers in rats with type II diabetes mellitus (54).…”
Section: Diabetes and Metabolismsupporting
confidence: 69%
“…Ultimately, the above processes may culminate a progressive destruction (apoptosis) of the bcells. However, it must be noted that there are marked species differences in the regulation of CSE expression in islets (65). For instance, H 2 S production can be increased by hyperglycemia, which has been observed in mouse islets and MIN6 cells (65), but not in rat insulinoma cells (80).…”
Section: Role Of H 2 S In the Pathogenesis Of Autoimmune B-cellmentioning
confidence: 99%
“…1 Though several etiological background of this non-communicable epidemic disease has been well explained and being efficiently treated, yet, a number of recent literatures suggested a potential role of H 2 S and H 2 S modifying agents in the etiology and management of this metabolic disorder. 2 Hydrogen sulfide is endogenously produced in the mammalian tissues from the amino acid L-cysteine by the action of two enzymes, cystathionine beta-synthase (CBS) and cystathionine gamma-lyase (CSE). Both of these enzymes are dependent on pyridoxal-5'-phosphate.…”
Section: Introductionmentioning
confidence: 99%